Equilibrium concentration profiles of species in CO2-alkanolamine-water systems - Haji-Sulaiman, M.Z.; Aroua, M.K.; Pervez, M.I. (Gas Separation and Purification, 1996)
Equilibrium concentrations of species and gas loading in aqueous solutions of alkanolamine loaded with CO2 are being compared with predicted profiles obtained from the Deshmukh-Mather Model. A new technique is being proposed based on titration using a base, NaOH, to determine the concentrations of the different species at equilibrium. The technique is reliable and easy to perform to give reproducible results. Experimental and predicted concentrations of species are in good agreement over a range of gas loading between 0.4 and 1.0 for aqueous AMP solutions. For DEA, the predicted and measured values complement each other at high loading typically above 0.6. At low loading, there is a significant difference between the sets of values for carbamate and bicarbonate. These differences are likely due to the value of the equilibrium constant for the carbamate formation, which is taken as an adjustable parameter in the model, to give the best fit to the experimental data of either CO2 partial pressure or gas loading.